CD34+ cell mobilization, blood graft composition, and posttransplant recovery in myeloma patients compared to non‐Hodgkinʼs lymphoma patients: results of the prospective multicenter GOA study. Issue 7 (24th April 2020) - Turunen, Antti; Partanen, Anu; Valtola, Jaakko; Ropponen, Antti; Siitonen, Timo; Kuittinen, Outi; Kuitunen, Hanne; Putkonen, Mervi; Sankelo, Marja; Keskinen, Leena; Savolainen, Eeva‐Riitta; Pyörälä, Marja; et al.
Abstract : BACKGROUND: Autologous stem cell transplantation is an established treatment option for patients with multiple myeloma (MM) or non‐Hodgkinʼs lymphoma (NHL). STUDY DESIGN AND METHODS: In this prospective multicenter study, 147 patients with MM were compared with 136 patients with NHL regarding the mobilization and apheresis of blood CD34+ cells, cellular composition of infused blood grafts, posttransplant recovery, and outcome. RESULTS: Multiple myeloma patients mobilized CD34+ cells more effectively (6.3 × 10 6 /kg vs. 3.9 × 10 6 /kg, p = 0.001). The proportion of poor mobilizers (peak blood CD34+ cell count <20 × 10 6 /L) was higher in NHL patients (15% vs. 3%, p < 0.001). Plerixafor was added to rescue the mobilization failure in 17 MM patients (12%) and in 35 NHL patients (26%; p = 0.002). The infused grafts contained more natural killer (NK) and CD19+ cells in MM patients. Blood platelet and NK‐cell counts were higher in MM patients posttransplant. Early treatment‐related mortality was low in both groups, but NHL patients had a higher late (>100 days) nonrelapse mortality (NRM; 6% vs. 0%, p = 0.003). CONCLUSIONS: Non‐Hodgkinʼs lymphoma and MM patients differ in terms of mobilization of CD34+ cells, graft cellular composition, and posttransplant recovery. Thus, the optimal graft characteristics may also be different.